Servant Leadership, Hope Theory, and Future Orientation in Nigerian Agriculture - David, A. M.; Jaco, D. A. (Covenant Journal of Entrepreneurship, 2022)
This original study examined a relationship between the GLOBE Future Orientation (FO) cultural dimension, Hope theory, and Servant Leadership (SL) to influence hope in the Nigerian agricultural industry (House, Hanges, Javidan, Dorfman, & Gupta, 2004). The FO dimension has a solid relationship to the Hope Work construct. Servant Leadership theory should influence the organization, so we asked, can it increase hope in the organization? Three established surveys of hope theory, future orientation, and servant leadership were selected. The selection of participants in Nigeria relied on above high school education level workers at two corporate farms, with 61% being bilingual. The questionnaires were distributed in a convenience sampling to all employees with an above high school educational level present in two corporate farms. The FO measurements indicated that this group was satisfied with the current FO of their organization and did not believe improvements were needed or possible. Both Hope subscales indicate a high ability of the participants to use Hope theory within their organization. The connection between Hope theory and Servant Leadership individual behaviors showed little correlation. However, the finding that all SL behaviors used together demonstrates a strong correlation that can increase hope. Therefore, when all SL behaviors are used together, this recommendation can achieve workplace objectives that increase hope and will be greater than temporal, material gain with the expected results of servant leadership. In conclusion, the use of hope theory to SL behaviors can be an essential addition to improving worker hope in the agricultural industry.